2013
DOI: 10.1002/hep.26346
|View full text |Cite
|
Sign up to set email alerts
|

Cellular-specific role of toll-like receptor 4 in hepatic ischemia-reperfusion injury in mice

Abstract: Ischemia-reperfusion (I/R) injury is a process whereby an initial hypoxic insult and subsequent return of blood flow leads to the propagation of innate immune responses and organ injury. The necessity of the pattern recognition receptor, toll-like receptor (TLR)-4, for this innate immune response has been previously shown. However, TLR4 is present on various cell types of the liver, both immune and non-immune cells. Therefore, we sought to determine the role of TLR4 in individual cell populations, specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 37 publications
4
98
0
Order By: Relevance
“…Injection of recombinant HMGB1 exacerbates, whereas treatment with HMGB1-neutralizing antibody protects hepatic I/R damage in TLR4 wildtype mice, but not TLR4-deficient mice (38). In addition, TLR4 from parenchymal cells but not myeloid cells and DCs also regulates hepatic I/R-induced HMGB1 release by activation of reactive oxygen species and calcium/calmodulin-dependent protein kinase (CaMK) signaling pathway (38,40). Treatment with CaMK inhibitor (KN93) and antioxidant Nacetylcysteine inhibit HMGB1 release and protect against liver I/R injury in animal models.…”
Section: Hmgb1 and Liver I/rmentioning
confidence: 99%
“…Injection of recombinant HMGB1 exacerbates, whereas treatment with HMGB1-neutralizing antibody protects hepatic I/R damage in TLR4 wildtype mice, but not TLR4-deficient mice (38). In addition, TLR4 from parenchymal cells but not myeloid cells and DCs also regulates hepatic I/R-induced HMGB1 release by activation of reactive oxygen species and calcium/calmodulin-dependent protein kinase (CaMK) signaling pathway (38,40). Treatment with CaMK inhibitor (KN93) and antioxidant Nacetylcysteine inhibit HMGB1 release and protect against liver I/R injury in animal models.…”
Section: Hmgb1 and Liver I/rmentioning
confidence: 99%
“…9 The sterile immune response is the main cause of toxicity and cell death during warm ischemia, where ROS signaling is sustained during reperfusion. 10 In contrast, other studies have shown that ROS derived from Kupffer cells are essential for I/R liver injury. Activated Kupffer cells significantly increase their release of ROS and proinflammatory cytokines, including TNF-α, IL-1, INFγ, and IL-12.…”
mentioning
confidence: 93%
“…Liver I/R injury can activate TLR4 through ATP generation, cellular ion (especially calcium [Ca 2+ ]) homeostasis, and generation of reactive oxygen species [9]. Ca 2+ plays as a major second messenger role in regulating a broad range of important cellular processes.…”
Section: Introductionmentioning
confidence: 99%